Spectroscopic and Electrochemical Properties of 1- or 2-alkyl Substituted 5- and 6-Nitroindazoles - Kouakou, Assoman; Micheletti, Gabriele; Boga, Carla; Calvaresi, Matteo; Chicha, Hakima; Franchi, Paola; Guadagnini, Lorella; Lucarini, Marco; Rakib, El Mostapha; Spinelli, Domenico; Tonelli, Domenica (Current Organic Chemistry, 2015)
In the framework of our general interest on the reactivity and on the pharmacological activity of heterocyclic compounds, we have examined the behaviour of some variously substituted 5- and 6-nitroindazoles. Remembering that nitroreduction processes are often essential steps for their biological activity we have collected NMR, ESR, and CV data and carried out DFT computations to gain a deep picture of electronic distribution and of reduction processes as a function of the chemical structure of the examined substrates. Interestingly, DFT computations have furnished strong support to experimental data. Moreover, the comparison between the general behaviour of 1- and 2-alkyl substituted nitroindazoles has furnished further confirmation to the known different electronic distribution in these two classes of compounds, while CV data have evidenced the ability of N1-H nitroindazoles to give rise to the formation of a dimer.
Keywords: NMR spectroscopy